Specialization training of doctors in the surgical specialties in Poland - Justyna Grudziąż-Sękowska; Agnieszka Bauman; Magdalena Kapica; Piotr Jankowski; Małgorzata Wywrot; Urszula Religioni; Aurelia Ostrowska; Jarosław Pinkas; Janusz Ostrowski; Wojciech Stefan Zgliczyński (Wiedza Medyczna, 2022)
Introduction: The specialisation education system in Poland is subject to constant changes, the aim of which is to adapt it to changing needs, while ensuring the highest quality of education. The need for reform is indicated by the doctors themselves who undergo specialisation training, and who know its strengths and weaknesses best. Potential changes should be evaluated and implemented on an ongoing basis to ensure the continuous development of the specialisation education system. Moreover, the quality of education should be constantly monitored to maintain its appropriate level.Aim of the article: The study aims to characterize the changes taking place in the system of specialisation education in nine selected treatment areas of medicine as well as in anaesthesiology and intensive therapy in 2011-2020, with particular emphasis on quantitative changes.Material and methods: The material for analysis consists of data from the register of doctors undergoing specialisation training conducted by the Centre of Postgraduate Medical Education of Warsaw (CMKP) from 2011 to 2020, data provided by The Supreme Medical Chamber (NIL) and the Medical Examinations Centre (CEM) in 2011-2018. The material analysis was quantitative and was carried out with the use of Microsoft Excel.Results: The data analysis carried out indicates that in the analysed set of specialisations in 2011-2020:the number of doctors undergoing specialisation training has increased,the share of doctors undergoing specialisation training as part of residency has increased,the share of women in the group of doctors undergoing specialisation increased,the number of training places has increased,the number of accredited units has increased,the use of training places has decreased (the number of training places per specialist doctor has increased), andthe average age of a person undergoing specialisation has decreased.Conclusions: The postgraduate education system for doctors in Poland in 2011-2020 was subject to numerous reforms and was constantly developing. Modular Specialisations have been introduced to improve accessibility and reduce the time to complete Specialisations that were formerly Detailed Specialisations. The number of doctors in  in the surgical specialisations in Poland  shows a growing trend.